ERH facilitates microRNA maturation through the interaction with the N-terminus of DGCR8 - Kwon, S Chul (Nucleic Acids Res, 2020)
The microprocessor complex cleaves the primary transcript of microRNA (pri-miRNA) to initiate miRNA maturation. Microprocessor is known to consist of RNase III DROSHA and dsRNA-binding DGCR8. Here, we identify Enhancer of Rudimentary Homolog (ERH) as a new component of Microprocessor. Through a crystal structure and biochemical experiments, we reveal that ERH uses its hydrophobic groove to bind to a conserved region in the N-terminus of DGCR8, in a 2:2 stoichiometry. Knock-down of ERH or deletion of the DGCR8 N-terminus results in a reduced processing of suboptimal pri-miRNAs in polycistronic miRNA clusters. ERH increases the processing of suboptimal pri-miR-451 in a manner dependent on its neighboring pri-miR-144. Thus, the ERH dimer may mediate ‘cluster assistance’ in which Microprocessor is loaded onto a poor substrate with help from a high-affinity substrate in the same cluster. Our study reveals a role of ERH in the miRNA biogenesis pathway.